Teknik pembuatan kerupuk bawang ikan bandeng (Chanos chanos) untuk pemberdayaan perempuan di Gampong Ulee Pulo Kabupaten Aceh Utara (Processing techniques of onion crackers from milk fish (Chanos chanos) for women empowerment at Ulee Pulo Village District of Aceh Utara) - Ayuzar, Eva; Muliani, M; Adhar, Saiful; Rahman, Arief (Buletin Pengabdian, 2021)
The purpose of this community service is to increase the knowledge of women in the village of Ulee Pulo, North Aceh Regency, Indonesia about processing techniques of pond cultivation products, namely milkfish onion crackers. This community service activity used a survey method and direct outreach. The survey consisted of determining the location and the group, while the outreach consisted of preparing materials and tools, processing, and organoleptic testing (scoring test). The components of the organoleptic test consisted of taste, odor, shape, color, and savory. Panelists who gave organoleptic test assessments included village apparatus, lecturers, and the community with a total of 25 panelists. Questionnaires were used to see the level of success of the activity. The observation results of the activity, it is known that this activity can improve the knowledge of women in family welfare empowerment group(Pemberdayaan Kesejahteraan Keluarga/PKK)in processing milkfish into onion crackers. Also, the added value of milkfish can increase especially when the harvest is abundant. Organoleptic test results showed that color score 5(Yellow-brown), odor 4,3 (the scent of milkfish), texture 5 (crunchy), salty taste 5 (salty ideal), savory taste 4,6 (tasty).